Community and Individuals at Emar - Viano, Maurizio (Altorientalische Forschungen, 2010)
The present article aims to investigate the connections between the Emar’s socio-political structures and the system of land-ownership that had different traits compared to other Syrian cities of the Late Bronze Age. The city of Emar and its region show a strong tradition of collective powers which goes back to the third millennium and influenced the society during the Late Bronze Age as well, but as this paper puts forward the land-ownership was individual.